Malay-Based Islamic Education: Character Building in the Digitized Era - Nur Azmira; Haris Riadi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Malay Islamic education plays an important role in shaping the character, morality, and identity of society; however, in the era of social media, these values face challenges arising from the rapid flow of information, changing interaction patterns, and the weakening of scientific authority. On the other hand, digitalisation also provides opportunities for the development of Islamic preaching, learning, and technology-based access to knowledge. This study aims to examine the role of Malay Islamic education in strengthening the character of younger generations in the digital era. The study employed a qualitative descriptive method through a literature review of classical and contemporary sources related to Malay Islamic education, adab, digital culture, and technological literacy. The findings reveal that Malay Islamic education, developed through surau, madrasahs, and Islamic boarding schools, not only strengthens religious understanding but also instils character values, social ethics, and adab as moral filters in the use of digital technology. These values are relevant in shaping younger generations who are moral, critical, and wise in responding to technological developments in the social media era. Therefore, the strengthening of Malay Islamic education should continue to be integrated with digital literacy in a contextual and sustainable manner.